2016
DOI: 10.1111/aab.12311
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment with salicylic acid invokes defence mechanism ofHelianthus annuusagainstOrobanche cumana

Abstract: The root holoparasitic angiosperm sunflower broomrape (Orobanche cumana) specifically affects sunflower (Helianthus annuus) growth and causes severe damage all over the world. This investigation was designed to examine the protective effects of salicylic acid (SA) treatment to the seeds of an O. cumana-susceptible cultivar of sunflower (TK0409). Sunflower seeds were pretreated with different concentrations (0, 0.5 and 1 mM) of SA and inoculated with O. cumana for 4 weeks. O. cumana infection resulted in reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 83 publications
1
17
0
1
Order By: Relevance
“…However, a foliar application of BTH did not complement the loss of SA in NahG rice plants, suggesting that BTH and endogenous SA may have different effects on S. hermonthica resistance in rice [24]. Sunflower seeds pretreated with SA and then grown in pots containing O. cumana seeds showed an increased biomass via reducing the number and biomass of established O. cumana, suggesting that the treatment invokes a defence mechanism of the host against the parasite [205].…”
Section: Sa-and Ja-mediated Plant Defence Responsesmentioning
confidence: 97%
“…However, a foliar application of BTH did not complement the loss of SA in NahG rice plants, suggesting that BTH and endogenous SA may have different effects on S. hermonthica resistance in rice [24]. Sunflower seeds pretreated with SA and then grown in pots containing O. cumana seeds showed an increased biomass via reducing the number and biomass of established O. cumana, suggesting that the treatment invokes a defence mechanism of the host against the parasite [205].…”
Section: Sa-and Ja-mediated Plant Defence Responsesmentioning
confidence: 97%
“…Sunflower seed treatment with SA reduced the Orobanche cumana biomass and improved sunflower growth. Moreover, SA treatment increased hydrogen peroxide content in sunflower by 14% (Yang et al, ). Thereby, there is disagreement in determining the role of signalling pathways against broomrape.…”
Section: Discussionmentioning
confidence: 99%
“…These cases showed that broomrape does not activate the SA pathway. Interestingly though, the artificial activation of the SA pathway slightly increased the host's resistance to broomrape (Hurtado, 2004 (Yang et al, 2016). Thereby, there is disagreement in determining the role of signalling pathways against broomrape.…”
Section: Discussionmentioning
confidence: 99%
“…Seed treatment with JA also changes the volatile composition of mature plants, making their blends more attractive to predatory mites (Smart et al , 2013). Similarly, seed treatment with salicylic acid (SA) enhances the expression of SA-related genes and the endogenous SA level against root holoparasite ( Orobanche cumana ) (Yang et al , 2016). Additionally, seed coating with plant growth promoting rhizobacteria (PGPR) and plant growth promoting fungus (PGPF) enhances seed germination, seedling establishment, and boosts induced defenses in future plants in SA-, ET-, and JA-dependent manners (Ryu et al , 2004; Rudrappa et al , 2010; Sharifi & Ryu, 2016).…”
Section: Introductionmentioning
confidence: 99%